Severe Injury Caused by a Traumatic Toothbrush Impalement: A Case Report - Islas, María (2016)
The present report describes a unusual case about a buccodental trauma in a 5-year-old boy, who suffered a wound by toothbrush impalement into the oral mucosa, between the ascendant ramus and the cheek vestibule, also the diagnostic process and hospital treatment, since his admission to the urgency room, the injury surgical management, and the postoperative control.